Plant Regeneration from Callus Culture in Arabidopsis thaliana (L.) (Bangladesh Journal of Genetics and Biotechnology, 2009)
Keywords: Arabidopsis thaliana; callus induction; plant regeneration Bangladesh j. genet. biotechnol. 7 (1&2): 99-101, 2006 (June & December)